PENGARUH KONTEN CHANNEL YOUTUBE JURNALRISA TERHADAP OPINI SUBSCRIBER TENTANG KONTEN MISTIS - Celine Hartati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Akit community in Sungai Tohor Barat Village, the majority did not go to school because the background of the primitive Akit tribe towards education was coupled with the socio-economic conditions of the Akit community who did not place much importance on their children's education. The formulation of the problem in this study looks at the meaning of education for the Akit Nerlang in Sungai Tohor Barat Village and knows how the cultural reproduction of the Akit Nerlang Tribe in Sungai Tohor Barat Village. Researchers used descriptive qualitative analysis by assigning 9 research subjects to 5 informants and 4 key informants who were taken intentionally (purposive sumpling) with criteria set by researchers. This study uses the theory of Habitus according to Pierre Bourdieu which is the result of learning through nurturing, playing activities, education. To understand the arena of cultural production, where the positions occupied by agents, namely schools, students, and parents are also occupied by the forces that make a cultural population, as well as an analysis of positions within the broader arena of power. The Akit people today interpret education as limited to literacy. The process of cultural reproduction occurs because parents assume that children are no longer interested in school and are forced to end up in vain, so that many are still out of school and choose to work. The results of this study indicate that the Akit tribal habitus interpret an education as not important, this also occurs due to the migration of people from one area to another can lead to cultural reproduction because they are difficult to accept new things where they still maintain local culture even though they are in different environment. In addition, the socio-economic conditions of the Akit people are still relatively low, in terms of social aspects, namely not accepting new things in education. Keywords : Cultural Reproduction, Akit Tribe, Sungai Tohor Barat Village